Application of Iot Features in Parking System - Yusof, Umar Hakimi; Hamzah, Mohd Hamdi Irwan (Applied Information Technology And Computer Science, 2021)
Parking is an important aspect of determining the scale of functionalities of building in modern days. The parking facilities during modern days are implementing modern appliances technology such as the usage of Internet of Things (IOT) techniques to its usability. IOT techniques are implemented throughout the usage of electronic sensors that detects the physical substances to be sent to the process section of the model. There were problems that exists in the current system that are been implemented by the OrangeBeam SDN BHD. The problems that is currently exists is the guards are required to routinely checks the parking spaces to determine availability of the parking spaces. Next, the parking cannot determine the exact amount of time used by a vehicle in the parking spaces. The objectives of this project are to design an IOT parking model for by using structured approach. Next, to develop a functioning IOT parking model. Lastly, to evaluate the developed IOT parking model. The methodology that been used during this project is Prototyping Model. This model was implemented during the prototype creation and subsequently gathered feedback from user to check if the developed product is good enough. This model allows the product to be developed with customer’s requirements and concerns. The project is expecting a functioning IOT model that will be paired with an application connected to it specifically. This project will hopefully able to influenced the public to use the IOT technologies to it fullest potential in order to improves each aspects our live exponentially